Retrospective reconstruction of Iodine-131 distribution through the analysis of Iodine-129 - Matsuzaki Hiroyuki; Muramatsu Yasuyuki; Ohno Takeshi; Mao Wei (EPJ Web of Conferences, 2017)
Iodine-131 distribution released from the Fukushima Dai-ichi Nuclear Power Plant accident was reconstructed through the iodine-129 measurements. From nearly 1,000 surface soil samples iodine was extracted by the pyro hydrolysis method. Extracted iodine was then mixed with carrier, purified and finally collected as silver iodide. Silver iodide sample was pressed into the cathode holder and set at the ion source of the MALT facility, The University of Tokyo. The isotopic ratio 129I/127I was measured by means of Accelerator Mass Spectrometry. From 129I data obtained, 131I deposition map was constructed. There observed various fine structures in the map which could not estimated neither by the simulation nor 137Cs distribution.